HUBUNGAN SUPERVISI KLINIS MANAJERIAL DENGAN KEPUASAN KERJA PERAWAT - Juliana, Juliana (Jurnal Mutiara Kesehatan Masyarakat, 2017)
Correct clinical supervision of ward heads can improve work satisfaction of nurse practitioners. The research was an quantitative study with a descriptive correlation design with cross sectional approach which was aimed to analyze the correlation between clinical supervision and nurses’ work satisfaction. It was conducted at Haji Hospital, Medan. The population was 156 nurses, and 140 of them were used as the samples, taken by using total sampling technique. The data were analyzed by using univatriate analysis and bivatriate analysis with Chi-square. The results showed that the clinical supervision of the managerial function in the good category was 54.3% and the nurses stated that the satisfaction was less than 97,1%. Good implementation of clinical supervision will potentially increase nurses’ work satisfaction and the continued existence of clinical supervision needs support from nursing care institution. It is suggested to the head of Imelda Hospital Medan to send the heads of the room to attend training related to the clinical supervision so that in the execution of his duty can give more support and motivate the nurse in carrying out nursing care. Keywords: clinical supervision, work satisfaction, nurse.